Étude comparative entre d’eux agrumes : la clémentine et le pamplemousse - MOHAMED-SEGHIR, NOURIA (My University, 2023)
Citrus, this colorful fruit is a treasure trove of vitamins and minerals that provide many health benefits. Like other fruits and vegetables, they are an important source of various antioxidants (phenolic compounds, flavonoids, ascorbic acid......etc). These compounds have beneficial effects on human health because they have many biological activities such as antioxidant, anti-inflammatory, and antibacterial activity. …… etc., which protects and prevents the harmful effects of free radicals on the human organism. Methanol extracts of clementine and grapefruit were tested for their antioxidant activities. The phenolic compounds (total polyphenols and flavonoids) extracted by the extraction solvent (methanol) present variations according to the extract and the variety, the evaluation of the antioxidant power in vitro revealed antioxidant capacities in all the extracts. For this several extraction methods were used the antioxidant activity of the extracts using techniques: DPPH radical trapping. The results obtained were very significant, and the correlation between the antioxidant activity and the content of total phenolic compounds was also studied. Our results showed that: • The total content of polyphenols in the methanolic extracts shows different results and is 446,07±64, 1817,80±94 μg. EA, corresponding respectively to the following extracts: Clementine, Grapefruit. • We observed that clementine has more flavonoid quantity of 891,20 ±84 μg EQ/mg, followed by grapefruit of 393,71±34 μg EQ/mg • All of our extracts contain significantly more antioxidant activities than those in the reference (ascorbic acid), clementine recorded in this study 915,746 μg /ml, this value remains significantly lower than that of ascorbic acid (639,24μg/ml). And grapefruit recorded in this study 233,416 μg /ml, this value remains significantly lower than that of ascorbic acid (1751,68μg/ml).
Keywords: Citrus; polyphenols; flavonoids; antioxidant activity; DPPH